Magnetic refrigeration: a promising new technology for energy saving. Issue 3 (3rd May 2016) - Aprea, C.; Greco, A.; Maiorino, A.
Abstract : Magnetic refrigeration is an emerging, environment-friendly technology based on a magnetic solid that acts as a refrigerant by magnetocaloric effect. The reference cycle for magnetic refrigeration is AMR (Active Magnetic Regenerative refrigeration). In this paper, attention is directed towards the near-room-temperature range. We compare the energetic performance of a commercial R134a refrigeration plant to that of a magnetic refrigerator working with an AMR cycle. The comparison is carried out by means of a mathematical model. In these simulations, we consider different solid magnetic refrigerants, namely, Gd, Gd0.95 Dy0.05, Gd0.9 Tb0.1, Gd5 Si2 Ge2, MnAs0.9 Sb0.1, and MnAs0.95 Sb0.05 . We compared two different geometries of the regenerator: a porous medium and a flat plate. In the former, the Coefficient of Performance (COP) of the AMR cycle is better than that of the vapour compression plant only in the low mass flow-rate range. Whereas in a flat plate regenerator, the COP of the AMR cycle is better than that of the vapour compression plant only in the high mass flow-rate range.